2007
DOI: 10.1902/jop.2007.060391
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Services Rendered by General Practitioners

Abstract: A variety of periodontal services were offered by GPs. The most common services were non-surgical in nature. Certain variables affected specific periodontal services rendered in general dental offices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 11 publications
5
36
0
Order By: Relevance
“…), well‐developed suburban (Greater Richmond area, Fredericksburg, Hampton Roads, etc. ), and remote rural areas (Southwest Virginia), which have been studied previously for referral patterns and rendering of periodontal services among GPs . These studies helped inform this current study design, adding to the documentation of perceptions of practicing dentists and periodontal specialists, where local trends could be the basis for a larger regional or national study.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…), well‐developed suburban (Greater Richmond area, Fredericksburg, Hampton Roads, etc. ), and remote rural areas (Southwest Virginia), which have been studied previously for referral patterns and rendering of periodontal services among GPs . These studies helped inform this current study design, adding to the documentation of perceptions of practicing dentists and periodontal specialists, where local trends could be the basis for a larger regional or national study.…”
Section: Methodsmentioning
confidence: 90%
“…An original list of questions was created and organized into five categories: 1) personal demographics; 2) demographics related to the periodontists’ primary practice; 3) distribution of referring dentists and perception of referral patterns (with internal and external referral being considered the same); 4) perception of treatment and practice model trends likely to impact periodontal practices; 5) likely adjustments needed to meet the demands of perceived trends in the dental market place. A literature search was conducted and questions were formed based on previously published studies of similar nature . After compiling questions, several practicing periodontists and members of the study team independently reviewed questions for clarity, consistency, and merit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical procedures to lengthen crowns not meeting this requirement involve using build‐up materials to replace lost tissue2 or adding grooves or boxes in the tooth 1. Alternatively, the amount of remaining tooth accessible for preparation can be improved by moving the tooth orthodontically3, 4 or repositioning the tissues surgically,5 a technique which is among the most commonly performed surgeries in general dental practices 6…”
Section: Introductionmentioning
confidence: 99%
“…An obvious strategy for sharing the burden of providing SPC is to delegate some provision of care to the referring general practitioner and hygienist. This would seem a reasonable approach given the observations made in a survey of periodontal services rendered by 600 general dental practitioners in Virginia, USA: In particular, that 50% of dentists provided SPC on a regular basis and 58% reported that 90% of scaling and root instrumentation was undertaken by one or more hygienists at the practice (Lanning et al 2007). Furthermore, as general dentists develop interests in periodontics through continuing education programmes (Lanning et al 2007) and as dental hygienists and therapists become more prevalent in the general dental services, then there may be a greater willingness to provide elements of the non‐surgical retreatment modality that is often required over and above the normal SPC (Fardal & Linden 2005).…”
mentioning
confidence: 99%